Upaya Peningkatan Ketahanan Pakan Domba Melalui Penanaman Hijauan Ternak dan Pembuatan Pakan Fermentasi di Dusun Kawang, Kabupaten Banyuwangi - Maghfirotul Amaniyah; Salvian Setyo Prayitno; Nanda Rusti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The Nagam Livestock Group as a partner is a group of novice farmers in Kawang Hamlet who need assistance in raising sheep, especially in providing feed. The partner's problem is the difficulty in providing feed due to limited time to find feed, as well as the fresh greens. The solution offered to partners are 1) conducting socialization of land optimization and making livestock feed, 2) training in planting feed seeds and making silage using a chopping machine, 3) evaluation of all of the activities. The results are that farmers have a new understanding in utilizing empty land through planting odot and indigofera grass. Making fermented feed (silage) supported by a grass chopping machine can produce silage products in larger quantities and of good quality. This Community Service Activity can contribute to the Kawang Hamlet Livestock Group by increasing the utility value of agricultural land and the availability of fermented feed